TP3-1 Memory impairment in epilepsy. Issue 3 (14th February 2019) - Wieshmann, UC; Chawira, A; Keller, S; Baker, G
Abstract : Objectives: Memory impairment is an extremely common complaint in people with epilepsy (PWE). The purpose of our cross sectional study was to identify factors associated with self-reported memory impairment in PWE. Methods: 514 PWE and 52 controls completed the Liverpool Adverse Event Profile, a 19 item questionnaire which includes items on memory and depression and provided clinical data on age, sex, medication, seizure onset, frequency and severity. For memory impairment, sleep disturbance, depression and seizure type scores were dichotomised into minor deficits (Likert scores 1 and 2), and major deficits (Likert scores 3 and 4). Results: In univariate analysis we found significant associations for mono vs polytherapy (χ2=14.85, p<0.001); minor/major depression (χ2=29.41, p<0.001); minor/major sleep disturbance (χ2=65.34, p<0.001); seizure freedom/persistence (χ2=14.40, p<0.001), the number of seizures in the last four weeks (p<0.001, U=17530.50, z=−5.11, but not sex, mean age of onset, mean duration of epilepsy or seizure type. Multinomial logistic regression revealed that sleep disturbance (p<0.001), AED poly therapy (p=0.004), depression (p<0.001) all retained significance whereas seizure persistence did not (p=0.377). Applying ANOVA to examine mean age with memory deficit outcomes, older age was significantly linked to poorer memory (F=3.34, p=0.002). Conclusions: Sleep disturbance, poly therapy and depression are potentially treatable factors associated with self-reported memory impairment in PWE.